1989
DOI: 10.1149/1.2096534
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalysis of Anodic Oxygen‐Transfer Reactions: Chloride‐Doped Lead Dioxide Electrodes

Abstract: The electrocatalytic activities were compared for pure and chloride‐doped normalbeta‐PbO2 films on gold and platinum substrates. Rate constants were increased significantly for oxidations of Mn2+, toluene, benzyl alcohol, dimethylsulfoxide and benzaldehyde in acidic media by the incorporation of Cl− into the oxide films. These reactions are concluded to occur by the electrocatalytic transfer of oxygen from H2O to the reaction products. Results of x‐ray diffraction studies indicate the Cl−‐doped PbO2 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…4 and are summarized in Table I. It is readily confirmed that the 0-transfer activity of the [3] and speculated that the higher activity might be the result of a small quantity of Fe(II1) in the oxide as a result of dissolution of the substrate during deposition. The voltammetric response of CN-is shown in Fig.…”
mentioning
confidence: 68%
“…4 and are summarized in Table I. It is readily confirmed that the 0-transfer activity of the [3] and speculated that the higher activity might be the result of a small quantity of Fe(II1) in the oxide as a result of dissolution of the substrate during deposition. The voltammetric response of CN-is shown in Fig.…”
mentioning
confidence: 68%
“…A small mirror was placed under the electrolysis cell for observing the variation of color at the electrode. All other instrumentation has been described [3]. All potential values are given vs. the standard calomel electrode (SCE) reference.…”
Section: Methodsmentioning
confidence: 99%
“…Notable values are: 21 % at P-PbO, in 2 M HPF, (750 mA ern-,, 0 "C) [3], 35% at glassy 63 carbon (GC) in 7.3 M HBF, (600 mA cm-27 0 "C) [9], and 45% at GC in 62 wt % HBF, Pt (200 mA cm-2, -5 "C) [lo]. Here we compare the 03-evolution at Fe(II1)-doped and…”
Section: Dmentioning
confidence: 99%
See 2 more Smart Citations